CAPOEIRA AS PATRIMONIAL EDUCATION: STUDY ON QUIBUNGO CAPOEIRA IN OCARA, CEARÁ - Cordeiro do Vale Xavier, Lisimére; Roberto Xavier, Antônio; Martinho Rodrigues, Rui; Gerardo Vasconcelos, José; Rogério Santana, José (LINKSCIENCEPLACE, 2026)
This work has as its main scope the general and specific approach of a capoeira. Thus, part of the general premise already established that capoeira integrates the cultural heritage of the Brazilian people as part of its history and memory and as such, needs to be linked and worked in the area of heritage education, especially in formal school spaces aimed at developing The sense of belonging and identity of Brazilian society. (UNESCO), the Roda de Capoeira became an integral part of the representative relationship of the World Cultural Heritage of Humanity recognized by the United Nations Educational, Scientific and Cultural Organization (UNESCO). In Brazil, a capoeira practice, as well as being part of the cultural and immaterial material heritage of the Brazilian people, is part of the national curricular context, and should be practiced, disseminated and expanded continuously. In this sense, heritage education is an indispensable resource for this purpose. Finally, and why they are shown in the specific approach regarding Quibungo Capoeira in the municipality of Ocara, which is part of the school curriculum as didactic-pedagogical activity in the area of heritage education representative of the history, memory and identity source of the national, regional and local collectivity.